Gut microbiota and other factors associated with increased T cell regulation in HIV-exposed uninfected infants - Johnson, Michael J.; Lazarus, Sarah K.; Bennett, Ashlynn E.; Tovar-Salazar, Adriana; Robertson, Charles E.; Kofonow, Jennifer M.; Li, Shaobing; McCollister, Bruce; Nunes, Marta C.; Madhi, Shabir A.; Frank, Daniel N.; Weinberg, Adriana (Frontiers in Immunology, 2025)
IntroductionInfants exposed to HIV and uninfected (HEUs) are at higher risk of infectious morbidity than HIV-unexposed uninfected infants (HUUs). Multiple immune defects of unknown origin were observed in HEUs. We hypothesized that HEUs have more regulatory and inhibitory checkpoint-expressing T cells (Treg, Tici) than HUUs, which may dampen their immune defenses against pathogens.MethodWe used flow cytometry to measure 25 Treg/Tici subsets in HEUs and HUUs at birth, 6, 28, and 62 weeks of life. We used maternal and infant gut microbiome data reported in a previous study to establish correlations with the Treg/Tici.ResultsAt birth, 3 Treg subsets, including the prototypic CD4+FOXP3+ and CD4+FOXP3+CD25+, had higher frequencies in 123 HEUs than in 117 HUUs, and 3 subsets had higher frequencies in HUUs. At 28 and 62 weeks of age, 5 Treg/Tici subsets had higher proportions in HEUs than HUUs. The frequencies of the Treg/Tici subsets that diverged between HEUs and HUUs at birth correlated with differential relative abundances of bacterial taxa in the maternal gut microbiome. The Treg/Tici subsets with significantly different frequencies at subsequent visits correlated with the concurrent composition of the infant gut microbiome. In vitro, treatment of HUU peripheral blood mononuclear cells (PBMC) with bacterial taxa most abundant in HEUs expanded Treg/Tici subsets with higher frequencies in HEUs than HUUs, recapitulating the in vivo correlations. Conversely, in vitro treatment of HEU PBMC did not increase Treg/Tici frequencies. Other factors that correlated with increased Treg/Tici frequencies were low maternal CD4+ T cells in HEUs at birth and male sex in the HUUs at 28 weeks of life.DiscussionThis study shows that maternal and infant gut dysbiosis are central to the increase in Treg/Tici in HEUs and may be targeted by mitigating interventions.